Design of Colloidally Stable and Non‐Toxic Petox‐Based Polymersomes for Cargo Molecule Encapsulation. Issue 6 (18th April 2019) - Oz, Umut Can; Kucukturkmen, Berrin; Ozkose, Umut Ugur; Gulyuz, Sevgi; Bolat, Zeynep Busra; Telci, Dilek; Sahin, Fikrettin; Yilmaz, Ozgur; Bozkir, Asuman
Abstract: Polymersomes are vesicular constructs formed by the self‐assembly of polymer amphiphiles. Here we report the fabrication of PEtOx‐ b ‐PLA polymersomes at physiological pH/salt concentration and the determination of a f PEtOx range, which is one of the most recognized factors that governs the self‐assembly of amphiphilic copolymers, for the first time. The findings indicate that PEtOx‐ b ‐PLA copolymers, containing PEtOx fractions of varied lengths, self‐assemble to form polymersomes in the range of 98.35 to 119.50 nm. The encapsulation potential of PEtOx‐ b ‐PLA polymersomes was demonstrated by loading of docetaxel (hydrophobic) with 17.90% encapsulation efficiency and by loading of pDNA (hydrophilic) with 65.03% encapsulation efficiency. In addition, size distribution profiles showed that polymersomes are colloidally stable for 24 h at 37 °C and for 3 months at +4 °C. The cell viability results showed that PEtOx‐ b ‐PLA copolymer and polymersomes are not cytotoxic to HUVEC, HEK293 and hMSC cell lines. Abstract : PEtOx‐ b ‐PLA based polymersomes were fabricated for the first time and the f PEtOx range for self‐assembly into vesicles has been described. Docetaxel and pDNA were successfully encapsulated into colloidally stable PEtOx‐ b ‐PLA polymersomes. The cell viability results indicate that PEtOx‐ b ‐PLA copolymer and polymersomes are non‐toxic.